1997
DOI: 10.1677/joe.0.1520211
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of anterior pituitary galanin and vasoactive intestinal peptide by oestrogen and prolactin status

Abstract: The neuropeptides vasoactive intestinal peptide (VIP) and galanin are synthesized in the anterior pituitary, galanin in the lactotroph and VIP probably in another cell type, and both stimulate prolactin secretion. Oestrogen regulates anterior pituitary VIP and galanin, galanin expression reflecting physiological variation in oestrogen status, whilst VIP is induced by pharmacological concentrations of oestrogen. Implanting anterior pituitaries under the renal capsule to induce hyperprolactinaemia we studied the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…Pituitary levels of prolactin mRNA and protein are markedly reduced in female GALKO mice (Wynick et al, 1998). Moreover, in addition to stimulating ethanol intake, GAL has a strong, stimulatory effect on the secretion of prolactin (Koshiyama et al, 1987; Ottlecz et al, 1988), which in turn can increase food intake (Cai et al, 1998; O’Halloran et al, 1991), and prolactin in E 2 -primed rats stimulates GAL (Hammond et al, 1997). Whereas there are no studies in female rats showing a causal effect of prolactin on ethanol intake, there is evidence that chronic consumption of ethanol increases circulating prolactin levels in females, while having no effect in males (Emanuele et al, 2001; Salonen and Huhtaniemi, 1990; Sanchis et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Pituitary levels of prolactin mRNA and protein are markedly reduced in female GALKO mice (Wynick et al, 1998). Moreover, in addition to stimulating ethanol intake, GAL has a strong, stimulatory effect on the secretion of prolactin (Koshiyama et al, 1987; Ottlecz et al, 1988), which in turn can increase food intake (Cai et al, 1998; O’Halloran et al, 1991), and prolactin in E 2 -primed rats stimulates GAL (Hammond et al, 1997). Whereas there are no studies in female rats showing a causal effect of prolactin on ethanol intake, there is evidence that chronic consumption of ethanol increases circulating prolactin levels in females, while having no effect in males (Emanuele et al, 2001; Salonen and Huhtaniemi, 1990; Sanchis et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…In the pituitaries of randomly cycling female rats there are more galanin-containing cells and galanin mRNA than in the pituitaries of males [17, 42], the highest concentrations being seen on the morning of estrus and the lowest concentrations on the morning of diestrus. It has also been reported that estrogen stimulates galanin gene expression [16, 17, 43] and galanin release from the pituitary [18]. In addition, estrogen up-regulates the sensitivity of the pituitary to galanin in vivo [40].…”
Section: Discussionmentioning
confidence: 99%
“…Several possibilities exist. It may be related to the known effects of E 2 and T 3 on the maintenance of lactotrope function and reactivity to TRH [1, 7, 35], and on the availability of pituitary paracrine/autocrine regulators such as VIP and galanin which stimulate basal PRL secretion [7]. E 2 or T 3 may also affect the receptor capacity, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Among these factors, 17β-estradiol (E 2 ), thyroid hormones, and thyrotropin-releasing hormone (TRH) are known to affect both synthesis and secretion of PRL [1, 5, 6, 7, 8]. E 2 and triiodothyronine (T 3 ) have also been shown to influence lactotrope responses to PRL inhibitory and stimulatory factors [4, 7, 9]. In addition, acetylcholine (ACh), synthesized in the pituitary, has been implicated as a local regulator of pituitary function [10, 11, 12].…”
Section: Introductionmentioning
confidence: 99%